2013
DOI: 10.1111/jpn.12045
|View full text |Cite
|
Sign up to set email alerts
|

Identification of undeclared sources of animal origin in canine dry foods used in dietary elimination trials

Abstract: SummaryFailure to respond to commercial limited antigen diets can occur in dogs kept on a dietary trial for the diagnosis of adverse food reaction (AFR). The aim of this study was to assess twelve canine dry limited antigen diets (eleven novel protein diets and one hydrolysed diet) for potential contamination by ingredients of animal origin not mentioned on the label. The validity of the two methods adopted for the detection of such food antigens was also evaluated. Each dietary product was analysed by microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 24 publications
(42 reference statements)
3
67
1
3
Order By: Relevance
“…Therefore, it is not easy to identify all of the protein sources with which the dog has come into contact 4, 7. Moreover, some commercial petfood diets, even those specified for an elimination dietary trial, contain animal proteins other than those declared in the ingredient list 8, 9. Vegetable proteins can be found in traces in pet food, but are less likely to cause allergic reactions 7.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is not easy to identify all of the protein sources with which the dog has come into contact 4, 7. Moreover, some commercial petfood diets, even those specified for an elimination dietary trial, contain animal proteins other than those declared in the ingredient list 8, 9. Vegetable proteins can be found in traces in pet food, but are less likely to cause allergic reactions 7.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently reported that there was extensive presence of proteins from undeclared animal sources even in specially formulated commercial limited-antigen diets designed for canine adverse food reaction [3]. There is therefore a case for the pet food industry to show greater transparency to customers by fully specifying the different types of animal proteins (animal species and tissue types) in their products.…”
Section: Resultsmentioning
confidence: 99%
“…Strict avoidance of the offending allergen is necessary to avoid relapses. However, accidental reactions are common, as allergens can be hidden in various foods or contaminate commercial food [22]. Lack of family member’s compliance and or the inappropriate food access can lead to undesired relapses.…”
Section: Discussionmentioning
confidence: 99%